Spermiogenesis and spermatozoon of the tapeworm Ligula intestinalis (Diphyllobothriidea): phylogenetic implications - Levron, Céline; Sitko, Jiljí; Scholz, Tomás (The Journal of parasitology, 2009)
Using transmission electron microscopy, spermiogenesis and the spermatozoon ultrastructural organization are described in Ligula intestinalis (Linnaeus, 1758) (Diphyllobothriidea), a parasite of the great crested grebe Podiceps cristatus (Linnaeus, 1758). Spermiogenesis starts with the differentiation zone of 2 striated rootlets, 2 centrioles giving rise to 2 flagella, and an intercentriolar body. The latter is composed of 5 electron-dense layers separating 4 electron-lucent layers. In the early stages of spermiogenesis, an electron-dense material is present in the apical region of the differentiation zone. Later, the flagella undergo a rotation and fuse with the cytoplasmic extension in a proximo-distal process. The spermatozoon contains 2 axonemes with a 9 + "1" trepaxonematan pattern, the nucleus, the cortical microtubules, and an electron-dense zone. The spermatozoon anterior extremity in L. intestinalis is characterized by the absence of crested bodies and a ring of electron-dense cortical microtubules. Some characters of spermiogenesis and spermatozoon in L. intestinalis confirm the recent splitting of "Pseudophyllidea" into 2 new orders, i.e., Bothriocephalidea and Diphyllobothriidea. The process of spermiogenesis is similar in both orders for the "type I" of spermiogenesis and the presence of electron-dense material. However, the intercentriolar body is clearly more developed in the Diphyllobothriidea than in the Bothriocephalidea. Moreover, these 2 orders seem to differ in the presence or absence of a ring of electron-dense cortical microtubules in the anterior extremity of the spermatozoon.
Keywords: ptáci; spermie; Cestode Infections; Birds; Spermatogenesis; Phylogeny; nemoci ptáků; zvířata; Male; fylogeneze; cestodózy; spermatogeneze; Czech Republic; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Spermatozoa; Animals; Bird Diseases; Česká republika; mužské pohlaví; Cestoda